1998
DOI: 10.1128/aem.64.4.1319-1322.1998
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Metal-EDTA Complexes by an Enriched Microbial Population

Abstract: A mixed culture utilizing EDTA as the sole carbon source was isolated from a mixed inoculum of water from the River Mersey (United Kingdom) and sludge from an industrial effluent treatment plant. Fourteen component organisms were isolated from the culture, including representatives of the genera Methylobacterium,Variovorax, Enterobacter,Aureobacterium, and Bacillus. The mixed culture biodegraded metal-EDTA complexes slowly; the biodegradability was in the order Fe>Cu>Co>Ni>Cd. By incorporation of i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(25 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…Sterile technique was used, although none of the Synechococcus and Prochlorococcus isolates used were axenic (Table 1). Marine bacteria can produce copper-binding compounds (Schreiber et al 1990) and can also degrade metal chelator complexes (Thomas et al 1998), so this was some cause for concern. By the end of the study, we had finally obtained an axenic culture of Prochlorococcus (Saito 2000), so we were able to do a control experiment to examine the effects of bacteria on our results.…”
Section: Methodsmentioning
confidence: 99%
“…Sterile technique was used, although none of the Synechococcus and Prochlorococcus isolates used were axenic (Table 1). Marine bacteria can produce copper-binding compounds (Schreiber et al 1990) and can also degrade metal chelator complexes (Thomas et al 1998), so this was some cause for concern. By the end of the study, we had finally obtained an axenic culture of Prochlorococcus (Saito 2000), so we were able to do a control experiment to examine the effects of bacteria on our results.…”
Section: Methodsmentioning
confidence: 99%
“…They had no illusions regarding the difficulty of treating these wastes [208]. In this expos e, Maszenan et al [208] cited the work of Bolton et al [209] and Thomas et al [210], showing that the practice and understanding of biodegradation did not significantly improve between 1996 and 2011.…”
Section: Metal Carboxylate-chelated Complexesmentioning
confidence: 98%
“…Games and Staubach [38] attempted to compare the rates of ozonation of unbound and chelated nitroloacetic acid (NTA, of Mg, Cu, and Zn); however, the results were inconclusive. Morooka et al [39] Biodegradation [198][199][200][201][202][203][204][205][206][207][208][209][210][211][212][213][214] Hybrid treatment methods [215][216][217][218][219][220][221] ozonolysed the EDTA chelates of Mg, Zn, and Cu and found that the rate of decomposition was in the following order: Mg > Zn > Cu. Gilbert and Hoffmann-Glewe [40] also compared the rates of ozonolysis of 1:1 EDTA chelates, studying the rate of degradation of EDTA (10 23 mol dm 23 ) by ozone in the presence of metallic ions.…”
Section: Ozonolysismentioning
confidence: 99%
“…that unde¢ned, rather complex systems were used. In such systems, EDTA was found to be degraded by mixed microbial consortia when added in the free form or as chelate of Cu 2 , Cd 2 , Zn 2 , Ni 2 , Mn 2 , Ca 2 or Fe 3 [149,153].…”
Section: Edtamentioning
confidence: 99%